Nepal School of Sociology/Anthropology - Bista, Dor Bahadur (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 1,493 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v1i0.1040 Occasional Papers on Sociology and Anthropology Vol.1 1987 p.6-10